The Role of Good Corporate Governance on Hospital Performance During Covid-19 - Susanto, Heri; Sirait, Afni; Maheresmi, Handani; Zuhrohtun, Zuhrohtun (Journal of International Conference Proceedings, 2023)
This study focuses on the role of corporate governance in mediating the relationship between the public sector, specifically government-owned hospitals, and financial performance during the COVID-19 pandemic. While there is existing research on corporate governance, there is limited attention given to the public sector and government hospitals in the context of the pandemic. The study highlights government hospitals as they are on the front lines of healthcare services during the pandemic and have experienced a significant influx of patients, particularly in COVID-19 referral hospitals. This has created financial challenges for hospitals, with increased workloads and disrupted cash flows. The objective of this study is to determine the extent to which corporate governance can help manage the financial difficulties faced by government hospitals during the pandemic. The findings of this research are expected to provide valuable insights for the government and hospital managers, aiding in the improvement of corporate governance and financial performance during emergencies such as the COVID-19 pandemic.